The Effect of Leverage, Liquidity, and Managerial Ownership on Financial Distress with Profitability as a Moderating Variable: On Transportation Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022 - Siti Aminah Dina Sinulingga; Erlina Erlina; Fahmi Natigor Nasution (International Journal of Economics, Management and Accounting, 2025)
Profitability acts as a moderating factor, this research seeks to learn how management ownership, leverage, and liquidity impact financial distress in transportation companies listed on the Indonesia Stock Exchange from 2018 to 2022. Quantitative research describes this kind of study. From 2018 through 2022, 37 transportation businesses were included in the study's population. These companies were listed on the Indonesia Stock Exchange (IDX). Eleven different businesses made up the sample. The kind of information used is secondary data. The method utilized to gather data is documentation studies. This study makes use of the Eviews 10 software program. The data analysis methods that are used include descriptive analysis, panel data regression analysis, R2 determination coefficient, significance test (t-test), and moderating test. According to the study's findings, financial distress is not significantly impacted by leverage, financial distress is negatively and significantly impacted by liquidity, financial distress is not significantly impacted by managerial ownership, and the relationship between the debt-to-equity ratio variable and financial distress cannot be moderated by profitability. However, profitability can moderate and strengthen the impact of liquidity on financial distress, and it can also moderate and strengthen the impact of managerial ownership on financial distress.